Spontaneous and induced fluorescence in the diagnosis of cancer of the digestive system: summary of previous communication - Badano Repetto, José Luis; Scolnik, Boris; Acosta Andreotti, Juan José; Lages, Saturnino; Badano Carbajal, José Luis (Cirugía del Uruguay, 2020)
The authors use the fluorescence provoked by tetracycline, its analogy and permanency in the neoplasic tissues, to detect them, so, the diagnosis becomes easier. They point out the existence of a fluorescence at the ultraviolet light, a natural one, in the· urine of the neoplasics, and they suggest it could be provoked by the presence of the called substancia "E", described in the neoplasics serum, by Dr. Esculies.